Alpheus inopinatus Holthuis & Gottlieb 1958 - Anker, Arthur; Al-Kandari, Manal; Grave, Sammy De (Zenodo, 2020)
Alpheus inopinatus Holthuis & Gottlieb, 1958 (Figs. 1, 3 A–C) Alpheus inopinatus Holthuis & Gottlieb 1958: 42, figs. 8, 9; Lewinsohn & Holthuis 1964: 51; Tirmizi & Kazmi 1969: 99 (379), fig. 1a; Karim & Hafizur 1974: 26, pl. 4, figs. 1–4b; Banner & Banner 1978: 223; Kazmi & Kazmi 1979: 153; Barkati 1980: 355; Kocataş 1981: 162; Banner & Banner 1982: 241, fig. 75; Lewinsohn & Galil 1982: 208; Afzal et al. 1986: 339; Jeng 1997: 13; Cunha et al . 2020: 343, 351, fig 5C–D, 6C–D, 7C–D. Alpheus lobidens. — Jones 1986: 152, pl. 42 ( partim ?); Geldiay 1969: 3, 5 (partim?); Kocataş & Kataĝan 2003: 65, 70 ( partim ?); Dehghani et al. 2019a: 486, fig. 4A–D ( partim ?) [not A. lobidens De Haan, 1849]. Alpheus sp. — Forest & Guinot 1958: 6, figs. 3–7 (see Banner & Banner 1982: 243). Material examined . Kuwait: 1 male, OUMNH. ZC.2020-01-001, Shaab, 29°21’16.78”N 48°01’47.38”E, mixed rocky-muddy intertidal, under rocks, leg. A. Anker, M. Al-Kandari, S. De Grave, Z. Sattari, 25 September 2019 [fcn KUW-011]; 1 male, OUMNH. ZC. 2020-01-002, same collection data as for previous specimen [fcn KUW-030]; 2 males, 1 female, OUMNH. ZC.2020-01-003, same collection data as for previous specimens [fcn KUW-034]; 1 male, OUMNH. ZC.2020-01-004, Failaka Island, eastern side, 29°23.409’N 48° 23.927’E, mixed rocky-muddy intertidal, under rocks, leg. M. Al-Kandari, 3 October 2019 [fcn KUW-077]; 1 male, 1 female, KISR, Al Julaia’a, Seashell Hotel, leg. M. Al-Kandari, 14 December 2019. Comparative material . Alpheus cf. lobidens De Haan, 1849. Kuwait: 1 male, 1 ovigerous female, OUMNH. ZC.2020-01-005, Ras Ajuza, 29°23.656’N 47°59.840’E, mixed rocky-muddy intertidal, under rocks, leg. M. Al-Kandari, Z. Sattari, 25 September 2019 [fcn KUW-027]; 1 female, OUMNH. ZC.2020-01-006, same collection data as for previous specimens [fcn KUW-029]; 1 male, OUMNH. ZC.2020-01-007, Shaab, 29°21’16.78”N 48°01’47.38”E, mixed rocky-muddy intertidal, under rocks, leg. A. Anker, M. Al-Kandari, S. De Grave, Z. Sattari, 25 September 2019 [fcn KUW-035]; 1 male, 1 ovigerous female, OUMNH. ZC.2020-01-008, same collection data as for previous specimen [fcn KUW-036]; 1 female, OUMNH. ZC.2020-01-009, Sulaibikhat Bay, 29°19.548’N 47°49.35’E, intertidal mud flat, in burrows, suction (yabby) pump, leg. A. Anker, M. Al-Kandari, Z. Sattari, 7 October 2019 [fcn KUW-107]; 1 male, 1 female, OUMNH. ZC.2020-01-010, same collection data as for previous specimen [fcn KUW-108]. Description . See Holthuis & Gottlieb (1958), Tirmizi & Kazmi (1969), Karim & Hafizur (1974) and Banner & Banner (1982). Colour pattern . Pale greenish or bluish grey to various tones of brown, often darker in females; pleon with three pairs of small dark spots distributed as following: one pair of small lateral spots on second pleuron, one pair of small dorsolateral spots on third pleuron (sometimes very faint and inconspicuous) and one pair of larger, more conspicuous lateral spots on fourth pleuron; mesial side of major and minor chelae greenish-brownish, with some olive or orange areas; dactylar plunger of major chela creamy white with some bluish tinge proximally; antennular and antennal flagella pale greenish-yellow; second pereiopods and walking legs (third to fifth pereiopods) pale reddish or pinkish with whitish articulations; tail fan brownish or greenish, with bluish area on uropodal exopod (Figs. 1, 3 A–C). General distribution . Possibly widely distributed in the Indo-West Pacific with records from the Red Sea, Djibouti, Arabian-Persian Gulf (Kuwait, Iran, see Remarks), Oman, Pakistan, Hong Kong, Taiwan, Australia (Tirmizi & Kazmi 1969; Banner & Banner 1978, 1981, 1982; Jeng 1997; present study); however, all records from outside of the western Indian Ocean require confirmation (see Remarks). Lessepsian migrant with a well-established population in the eastern Mediterranean Sea, with confirmed records from Israel and Turkey (Holthuis & Gottlieb 1958; Kocataş 1981; Lewinsohn & Galil 1982). Ecology . Largely intertidal, sometimes also in the shallow subtidal (to at least 6 m), rocky and mixed sandyrocky shores, often heavily silted or with a significant mud component; typically on sand/mud under large rocks and coral rubble (Lewinsohn & Galil 1982; present study). Remarks . Alpheus inopinatus belongs to the A. lobidens De Haan, 1849 species complex, together with A. crassimanus Heller, 1862 (currently considered to be a synonym of A. lobidens ), A. lobidens polynesicus Banner & Banner, 1974 (originally described as A. lobidens polynesica ), and the recently described A. mohammadpouri Dehghani, Sari & Naderloo, 2019 (Banner & Banner 1974, 1982; Dehghani et al. 2019b), together with a large number of undescribed species. The complicated taxonomic situation of A. lobidens and the presence of several cryptic or pseudocryptic species in this species complex make identifications of specimens extremely difficult (Anker & De Grave 2016). Alpheus inopinatus was originally described based on material from the Mediterranean coast of Israel, as an “immigrant from the Red Sea” (Holthuis & Gottlieb 1958). This species is morphologically very close to another species of the A. lobidens complex, which is present in the Gulf and possibly throughout the western and northern Indian Ocean (including the Red Sea), and identified either as A. lobidens (type locality: Japan) or A. crassimanus (type locality: Nicobar Islands, India). Like A. inopinatus , this species also penetrated into the Mediterranean Sea through the Suez Canal, spreading along the North African coasts from Egypt westwards to Tunisia, and northwards to Syria and Turkey (Hasan et al. 2008; Bakir et al. 2015). Older Mediterranean records of this species are under the name A. crassimanus (e.g., Balss 1936; Forest & Guinot 1956, 1958; Holthuis & Gottlieb 1958; Geldiay 1969), which was later placed in the synonymy of A. lobidens (see discussion in Banner & Banner 1974, 1981, 1982), with more recent records under the name A. lobidens (e.g., Bakir et al. 2015). In the present study, we tentatively continue to accept the synonymy of A. crassimanus with A. lobidens proposed by Banner & Banner (1974, 1982), who compared the Japanese specimens they identified as A. lobidens with the material from other areas of the Indo-West Pacific. However, we feel that a thorough morphological and molecular study is needed to establish the true identity of this taxon in light of the fact that their view of A. lobidens as a single widespread species has now been refuted (see also Cunha et al. 2020). The colour pattern of A. crassimanus is currently unknown, which is especially relevant in light of growing evidence of the presence of several cryptic or pseudocryptic species within the A. lobidens complex distinguishable mainly by colour patterns, for instance, in Singapore (Anker & De Grave 2016), Taiwan (A. Anker, pers. obs.), Japan (K. Nomura, pers. comm.), and Iran (Dehghani et al. 2019a). Forest & Guinot (1958) were aware of the presence of two morphologically distinct species from the A. lobidens complex on the Mediterranean coast of Israel, viz. A. inopinatus (reported as Alpheus sp., as it was already being studied by Holthuis & Gottlieb) and A. lobidens (reported by them as A. crassimanus ). These authors also examined several specimens in Henri Coutière’s alpheid collection in the Muséum National d’Histoire Naturelle in Paris (MNHN), which morphologically corresponded well to A. inopinatus , viz. two specimens from the Gulf of Oman and a mixed lot from Djibouti, containing both A. inopinatus and A. lobidens . Interestingly, Holthuis & Gottlieb (1958) contrasted A. inopinatus with A. lobidens only superficially, comparing it with three more distantly related species of Alpheus , whereas Forest & Guinot (1958) provided a full account of the morphological differences between the two taxa (see below). Banner & Banner (1981, 1982) questioned the separation of A. inopinatus from A. lobidens and synonymised the former species. The Hawaiian subspecies, A. lobidens polynesicus, was also placed in the synonymy of A. lobidens , despite some rather striking colour pattern differences (Banner & Banner 1981). However, at least some of the synonymies proposed by Banner & Banner (1981, 1982) in the A. lobidens complex were premature (Anker 2001; Anker & De Grave 2016). New material collected throughout the Indo-West Pacific clearly shows that several features of the colour pattern, such as the presence or absence of dark transverse bands on the pleon, the presence or absence of dark spots on the sides of the pleon, the markings on the mesial side of the major and minor chelae and the colour of the dactylar plunger, may provide additional differentiating characters between the species of the A. lobidens complex (Anker & De Grave 2016; A. Anker, pers. obs., see also Fig. 3). De Grave & Fransen (2011) treated A. inopinatus as a valid species, but continued to list A. lobidens polynesicus as a junior synonym of A. lobidens . The present material confirms that A. inopinatus is clearly distinct from the west Indian Ocean taxon often recorded as A. lobidens and thus represents a valid species (see also Cunha et al. 2020 for molecular comparison). The common and widespread taxon from the western Indian Ocean (e.g., Red Sea, Gulf, Pakistan), which penetrated into the Mediterranean Sea most likely does not represent A. lobidens sensu De Haan (1849) from Japan and is herein referred to A. cf. lobidens (see Comparative material). Whether this taxon is identical to A. crassimanus sensu Heller (1862) remains to be shown. Alpheus inopinatus can be separated from A. cf. lobidens by at least three morphological characters, in addition to a small but consistent difference in their colour patterns. Both species can also be separated morphologically from A. lobidens polynesicus and A. mohammadpouri . The taxonomic status of these taxa will be discussed elsewhere, as part of a larger study of the A. lobidens complex. Many of the differentiating characters between A. inopinatus and A. cf. lobidens listed by Forest & Guinot (1958) were confirmed in the present material. The most important character separating the two species is the absence of a sharp distomesial tooth on the meri of the major and minor cheliped in the former species. In some specimens of A. inopinatus , the distomesial margin terminates in a subacute angle, sometimes protruding as a minute tooth, which is not the same structure as a much stronger acute tooth, situated slightly below the distomesial angle, in A. cf. lobidens (cf. Forest & Guinot 1958: figs. 1, 3, 4). The male minor cheliped has a much stouter merus and a stouter and more sculptured chela in A. inopinatus, compared to the noticeably slenderer merus and chela of A. cf. lobidens (cf. Forest & Guinot 1958: figs. 2, 5). The third and fourth pereiopods are also stouter in A. inopinatus , as expressed by the more inflated merus, with a length-width ratio of about 3.0 (cf. Forest & Guinot 1958: fig. 7) vs. more than 4.0 in A. cf. lobidens from Kuwait or the specimens from Australia identified as A. lobidens by Banner & Banner (1982: fig. 78f). In life, A. inopinatus and A. cf. lobidens can be separated by their colour patterns, although the difference is rather subtle. The pleon of A. inopinatus presents three pairs of small dark spots: one pair of lateral spots on the second pleuron, one pair of very small dorsolateral spots on the third pleuron and one pair of more conspicuous lateral spots on the fourth pleuron (Fig. 1); all these spots are absent in A. cf. lobidens (Fig. 2). The dactylar plunger of the major chela of both species is similar in colour, whitish with creamy or yellow tinge, although in A. inopinatus , the base of the plunger has a bluish tinge (Fig. 3C), whilst in A. cf. lobidens , the anterior surface has a more intense pale orange colour (Fig. 3F). The Iranian material of A. lobidens listed by Dehghani et al. (2019a) likely contains both A. inopinatus and A. cf. lobidens , based on an analysis of the colour patterns of the four illustrated individuals. Generally, many records under the name “ A. lobidens ” from the Gulf, Red Sea, Mediterranean Sea and other localities may refer to A. inopinatus as the two species have been commonly confused in the past, especially after the synonymisation of A. inopinatus by Banner & Banner (1981, 1982). Anker & De Grave (2016), while reporting A. lobidens (as A. lobidens sensu lato ) from Singapore, provided colour photographs of three different colour morphs, possibly three different species, of the A. lobidens species complex. They can be briefly described as (1) pleon non-banded, with two conspicuous lateral black spots on the second and fourth pleura and two small medially fused black spots on the dorsal surface of the fifth pleonite (Anker & De Grave 2016: fig. 16A, E); (2) pleon banded, with two small dorsolateral black spots on the third pleuron, two very large and conspicuous black lateral spots on the fourth pleuron and two smaller black lateral patches on the fifth pleuron ( idem .: fig. 16C, D); and (3) pleon non-banded, without spots ( idem .: fig. 17). The arrangement of the spots of the Singaporean specimens appears to be different from that of A. inopinatus . In addition, the dactylar plunger of the major chela of the two black-spotted colour morphs from Singapore is bright orange, which makes them clearly different from both A. inopinatus and the specimens herein identified as A. cf. lobidens , both with whitish-creamy plungers (Fig. 3C, F). Therefore, all material identified as A. inopinatus from outside of the western Indian Ocean (Hong Kong, Taiwan, Australia) needs to be carefully re-examined. These observations also contribute to the remaining uncertainty about the taxonomic status of A. crassimanus , currently regarded as a synonym of A. lobidens (see above). Recently, Cunha et al. (2020) redescribed A. lobidens from Nagasaki on the basis of what they considered to be topotypic specimens, collected from the vicinity of Nagasaki. However, the type locality of A. lobidens is Japan, i.e., the entire Japanese archipelago and not specifically Nagasaki (De Grave & Fransen 2011: 385). Only six species described in De Haan (1833 –1850) actually have a type locality that is geographically more restricted than merely Japan (see Yamagushi & Baba 1993), so it cannot be assumed that the holotype of A. lobidens was indeed collected in the Nagasaki area. Furthermore, it is well known that the botanical and zoological collections gathered by Von Siebold and Bürger, a part of which was studied by De Haan, came from all over Japan. For example, the type series of the giant spider crab Macrocheira kaempferi (Temminck) was collected in Suruga Province, further east, whereas their collection also contained cold-water decapods from much further north, e.g., Lithodes japonicus Von Siebold, now known as Paralithodes camtschaticus (Tilesius). The authors simply “…assumed that the topotypes from Shimabara, Nagasaki, Japan (RMNH PEG 25134) correspond to A. lobidens sensu stricto , i.e., are conspecifics of the damaged holotype …”, without a direct comparison to the holotype. Although it is possible that Cunha et al. (2020) did redescribe what in future could be considered as true A. lobidens (i.e. A. lobidens sensu De Haan, 1849), it should be noted that numerous species of the A. lobidens complex occur in Japan, an observation based primarily on the diversity of colour patterns (K. Nomura, pers. comm.). As no colour pattern was documented for A. lobidens sensu Cunha et al. (20202), any further comparison with other taxa is hindered, as it is obvious now that colour patterns, along with molecular analyses and morphology, will be crucial to resolve this challenging species complex. For example, in Singapore (Anker & De Grave 2016), Kuwait (present study) and some localities in eastern Australia (A. Anker, pers. obs.), two or more species of the A. lobidens complex occur syntopically, with the easiest separation between them being consistent differences in the colour patterns. Al-Maliky et al. ( 2017) reported and illustrated Alpheus edwardsii (Audouin, 1826) from Basrah area in Iraq. Although their photographs of preserved specimens are in very low resolution, the dorsal shoulder of the major chela is not overhanging the adjacent transverse groove ( idem : figs. 2, 3A), whilst the merus of the major cheliped seems to be armed with a strong distomesial tooth ( idem : fig. 3B, D). Therefore, the Iraqi material can be tentatively referred to A. cf. lobidens , as suggested by Al-Khandari et al. (2020: p. 254; mind a small error therein, read correctly: “ Al-Maliky et al. (2017), who erroneously reported A. lobidens as A. edwardsii from Shatt-Al-Basrah and Faw in Iraq.”). : Published as part of Anker, Arthur, Al-Kandari, Manal & Grave, Sammy De, 2020, Taxonomic notes on Alpheus inopinatus Holthuis & Gottlieb, 1958 and Alpheus cf lobidens De Haan, 1849 from Kuwait (Malacostraca: Decapoda: Alpheidae), pp. 189-197 in Zootaxa 4851 (1) on pages 190-195, DOI: 10.11646/zootaxa.4851.1.10, http://zenodo.org/record/4407192 : {"references": ["Holthuis, L. B. & Gottlieb, E. (1958) An annotated list of the Decapod Crustacea of the Mediterranean Coast of Israel, with an appendix listing the Decapoda of the eastern Mediterranean. Bulletin of the Research Council of Israel, 7 B, 1 - 126, pls. 1 - 3.", "Lewinsohn, C. & Holthuis, L. B. (1964) New records of decapod Crustacea from the Mediterranean coast of Israel and the eastern Mediterranean. Zoologische Mededelingen, 40, 45 - 63.", "Tirmizi, N. M. & Kazmi, M. A. (1969) The occurrence of Alpheus inopinatus Holthuis & Gottlieb, 1958 in the Arabian Sea (Decapoda, Alpheidae). Crustaceana, 16, 99 - 100. https: // doi. org / 10.1163 / 156854068 X 00250", "Karim, S. I. & Hafizur, R. (1974) On some Carides of Karachi coasts. Records of Zoological Survey, 6, 25 - 28, pls. 1 - 4.", "Banner, D. M. & Banner, A. H. (1978) Annotated checklist of alpheid and ogyridid shrimp from the Philippine Archipelago and the South China Sea. Micronesica, 14, 215 - 257.", "Kazmi, M. A. & Kazmi, Q. B. (1979) A check-list of marine caridean prawns of Pakistan. Biologia, 25, 151 - 157.", "Barkati, S. (1980) Sex ratio, fecundity and larval development of Alpheus inopinatus Holthuis and Gottlieb, 1958 (Crustacea, Decapoda, Caridea). Proceedings of the First Pakistan Congress of Zoology, B, 355 - 359.", "Kocatas, A. (1981) Liste preliminaires et repartition des crustaces decapodes des eaux turques. Rapports de la Commission Internationale de la Mer Mediterranee, 27, 161 - 162.", "Banner, D. M. & Banner, A. H. (1982) The Alpheid Shrimp of Australia, part III: the remaining alpheids, principally the genus Alpheus, and the family Ogyrididae. Records of the Australian Museum, 34, 1 - 357. https: // doi. org / 10.3853 / j. 0067 - 1975.34.1982.434", "Lewinsohn, C. & Galil, B. (1982). Notes on species of Alpheus (Crustacea Decapoda) from the Mediterranean coast of Israel. Quaderni del Laboratorio di Tecnologia della Pesca, Ancona, 3, 207 - 210.", "Afzal, M., Javed, A. & Barkati, S. (1986) Checklist, synonymy and key to the genera and species of alpheid shrimps of Karachi coast. Pakistan Journal of Agriculture Research, 7, 337 - 340.", "Jeng, M. S. (1997) Studies on the land and aquatic decapod crustacean fauna of the Kenting National Park (II). Conservation Research Report, 96, 1 - 66.", "Cunha, A. M., Terossi, M., Mantelatto, F. M. & Almeida, A. O. (2020) Delimiting the snapping shrimp Alpheus lobidens De Haan, 1849 (Caridea: Alpheidae) based on morphological and molecular data. Zootaxa, 4718 (3), 337 - 354. https: // doi. org / 10.11646 / zootaxa. 4718.3.3", "Jones. D. A. (1986) A field guide to the sea shores of Kuwait and the Arabian Gulf. University of Kuwait, Kuwait City, 192 pp.", "Geldiay, R. 1969. A report on the collection of Natantia (Crustacea, Decapoda) along the coast of Turkey from the eastern Mediterranean to the vicinity of Izmir. Scientific Reports of the Faculty of Science Ege University, 74, 1 - 17.", "Kocatas, A. & Katagan, T. (2003) The decapod crustacean fauna of the Turkish seas. Zoology in the Middle East, 29, 63 - 74. https: // doi. org / 10.1080 / 09397140.2003.10637971", "Dehghani, A., Sari A. & Naderloo, R. (2019 a) Annotated checklist of the snapping shrimps of the genus Alpheus Fabricius, 1798 (Crustacea: Decapoda: Alpheidae) from the Persian Gulf and Gulf of Oman, Iran. Zootaxa, 4544 (4), 479 - 504. https: // doi. org / 10.11646 / zootaxa. 4544.4.2", "Forest, J. & Guinot, D. (1958) Sur une collection de crustaces decapodes des cotes d'Israel. Bulletin of the Sea Fisheries Research Station of Israel, 15, 4 - 16.", "Banner, D. M. & Banner, A. H. (1981) Annotated checklist of the alpheid shrimp of the Red Sea and Gulf of Aden. Zoologische Verhandelingen, Leiden, 190, 1 - 99.", "Heller, C. (1862) Neue Crustaceen gesammelt wahrend der Weltumsegelung der k. k. Fregatte Novara. Zweiter vorlaufiger Beri- cht. Verhandlungen der Koeniglich-Kaiserlichen Zoologisch-Botanischen Gesellschaft, Wien, 28, 519 - 528.", "Banner, A. H. & Banner, D. M. (1974) Contributions to the knowledge of the alpheid shrimp of the Pacific Ocean, part XVII: Additional notes on the Hawaiian alpheids: new species, subspecies and some nomenclatorial changes. Pacific Science, 28, 423 - 437.", "Dehghani, A., Sari, A. & Naderloo, R. (2019 b) Three new species of narrowly endemic snapping shrimp, genus Alpheus (Decapoda: Caridea: Alpheidae) from the Persian Gulf. Journal of the Marine Biological Association of the United Kingdom, 99, 911 - 920. https: // doi. org / 10.1017 / S 0025315418000693", "Anker, A. & De Grave, S. (2016) An updated and annotated checklist of marine and brackish caridean shrimps of Singapore (Crustacea, Decapoda). Raffles Bulletin of Zoology, Supplement 34, 343 - 454.", "Hasan, H., Zeini, A. & Noel, P. Y. (2008) The marine decapod Crustacea of the area of Lattakia, Syria. Crustaceana, 81, 513 - 536. https: // doi. org / 10.1163 / 156854008784092175", "Bakir, K., Ilkyaz, A. T., Aydin, C. & Turkmen, G. (2015) The presence of Alpheus lobidens De Haan, 1849 (Decapoda, Alpheidae) on the Turkish Aegean Sea coast. Crustaceana, 88, 651 - 656. https: // doi. org / 10.1163 / 15685403 - 00003434", "Forest, J. & Guinot, D. (1956) Sur une collection de crustaces decapodes et stomatopodes des mers tunisiennes. Bulletin de la Station Oceanographique Salammbo, 53, 24 - 43.", "Anker, A. (2001) Two new species of snapping shrimps from the Indo-Pacific, with remarks on colour patterns and sibling species in Alpheidae (Crustacea: Caridea). Raffles Bulletin of Zoology, 49, 57 - 72.", "De Grave, S. & Fransen, C. H. J. M. (2011) Carideorum catalogus: the recent species of the dendrobranchiate, stenopodidean, procarididean and caridean shrimps (Crustacea: Decapoda). Zoologische Mededelingen, Leiden, 85, 195 - 589.", "De Haan, W. (1833 - 1850) Crustacea. In: von Siebold, P. F. (Ed.), Fauna Japonica sive descriptio animalium, quae in itinere per Japoniam, jussuet auspicilis superiorum, qui summum in India Batava Imperium tenent, suspecto, annis 1823 - 1830 collegit, notis, observationibus et dumbrationibus illustravit. Fasc. 1 - 8. Apud Auctorem, Lugduni Batavorum, xvii + xxxi + 244 pp., 74 pls. [pp. i-xvii + i-xxxi + 1 - 244, pls. 1 - 55 + A-Q + 1 + 2. pp. i-xxi + vii-xvii + ix-xvi + 1 - 243, pls. 1 - 55 + A-Q, Circ. pl. 2]", "Al-Maliky, T. H. Y., Al-Khafaji, K. K. & Khalaf, T. A. (2017) New records of the snapping shrimp Alpheus edwardsii (Audouin, 1826) (Crustacea: Alpheoidea) in Basrah, Iraq. Arthropods, 6, 47 - 53.", "Audouin, V. (1826) Explication sommaire des planches de crustaces de l'Egypte et de la Syrie, publiees par Jules-Cesar Savigny, Membre de l'Institut; offrant un expos des characteres naturels des genres avec la distinction des especes. Animaux invertebres. In: Description de l'Egypte ou receuil des observations et des recherches qui ont ete faites en Egypte pendant l'expedition de l'armee francaise, publie par les ordres de sa Majeste l'Empereur Napoleon le Grand. Imprimerie Imperiale, Paris, pp. 77 - 98."]}